Edward Said’s Orientalism and the Representation of the East in Gardens of Water by Alan Drew - Yana Maliyana (Passage, 2013)
This research paper is aimed to uncover the ways in which the western author, Alan Drew, represents the East culture in the novel Gardens of Water (2003). The research employs qualitative descriptive study with the content analysis approach. The analysis of the novel is done within the theoretical framework of Orientalism proposed by Edward Said (1978). The results of the analysis show that the representation of non-western people and cultures confirms orientalist point of view that puts the East and the West in a binary opposition and represents the East as inferior to the West. The study also proves that the author uses typical stereotyping in representing the East in the novel such as untrustworthy, rude, barbaric and traditional and also exposes the issue of patriarchy which is usually pinned into the East Culture. This representation of the East leads to the justification of the West imperialism and colonization toward the East. Keywords : Orientalism, orientalist, binary opposition, representation of the East, West Imperialism